INFLUENCE OF ORGANIZATIONAL CULTURE, SELF-EFFICIENCY AND JOB SATISFACTION ON WORK MOTIVATION (Study on Workers from Eastern Indonesia Working in North Aceh) - Weki; Yanita; Azhar; Sullaida (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
This study aims to analyze the influence of organizational culture, self-efficacy and job satisfaction on work motivation of workers from eastern Indonesia who work in North Aceh. The research method used is descriptive qualitative research method. The research data was obtained through questionnaires which were distributed to the respondents. The results showed that organizational culture, self-efficacy and job satisfaction had a positive and significant effect on the work motivation of workers from Eastern Indonesia who worked in North Aceh.